2021
DOI: 10.1785/0220200388
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Temporal and Spatial Estimation of the b-Value

Abstract: The estimation of the b-value of the Gutenberg–Richter law is of great importance in different seismological applications. However, its estimate is strongly dependent upon selecting a proper temporal and spatial scale, due to the multiscale nature of the seismicity. For this reason, we propose a novel approach (MUltiscale Spatial and Temporal estimation of the B-value [MUST-B]), which allows consistent estimation of the b-value, avoiding subjective “a priori” choices, by considering simultaneously different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…To further validate our methodology, we also compared the weighted likelihood approach with the novel MUST-B estimator introduced by García-Hernández et al [25]. This estimator avoids subjective biases in the choice of the window size by taking the median values of different b-values estimated using rolling windows of different lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further validate our methodology, we also compared the weighted likelihood approach with the novel MUST-B estimator introduced by García-Hernández et al [25]. This estimator avoids subjective biases in the choice of the window size by taking the median values of different b-values estimated using rolling windows of different lengths.…”
Section: Discussionmentioning
confidence: 99%
“…This estimator avoids subjective biases in the choice of the window size by taking the median values of different b-values estimated using rolling windows of different lengths. This method was successfully applied to the 2016-2017 central Italy seismic sequence; in our exercise, we retained the parameters' values described in García-Hernández et al [25]. Bayes Factor values suggest that our methodology performed better than MUST-B, for both the TABOO (ln(BF) = 3.1), and the CMT (ln(BF) = 6.1) catalogues, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…found a 𝑏-value variation during the course of the sequence, in particular (i) a drop after the Amatrice event (especially in the area to the north where the Norcia mainshock occurred afterward), interpreted as a still impending large earthquake, and (ii) a 𝑏-value increase « after the Norcia mainshock, interpreted as a substantially reduced chance for a further large event similar to the tectonic background rate. García-Hernăndez et al [2021] also observed a "marked drop of the 𝑏-value" after the Amatrice event (resolved spatially and in depth) and a recovery of the 𝑏-value to the background level after the Norcia mainshock; they exclude that these variations are caused by an increased 𝑀 c after the main events. However, those studies did not (i) use a high-resolution catalog, (ii) account for the complexity of the sequence including its depth-dependent structure, and (iii) resolve what happened in the days before the largest event (Norcia).…”
mentioning
confidence: 90%
“…These catalogues can help test hypothesis such as the predictive value of a spatiotemporal variations in terms of b-value (e.g., Gulia and Wiemer 19 ; García-Hernández et al . 20 ; Herrmann et al . 21 ).…”
Section: Background and Summarymentioning
confidence: 99%